Relationship of criminal proceedings to civil litigation, insolvency and tax proceedings - Pavel Kotlán (DANUBE: Law, Economics and Social Issues Review, 2020)
The main goal of this article is to clarify the nature of criminal proceedings and its relationship to civil litigation, insolvency and tax proceedings. The understanding of the purpose of the proceedings, the nature of the liability fulfilled in the proceedings and the principles on which the proceeding is based can facilitate the investigation of economic crime by the prosecuting authorities. The results of the work lead to the conclusion that key factors are the purposes of each proceedings and differences in the principles by which they are governed. But legal norms are not always unambiguous - for instance, in the issue of the so-called punitive damages, the relationship between collateral proceedings and insolvency proceedings or the nature of penalties under Art. 251 of the Tax Code.
Keywords: 330; Criminal Proceedings; Economic Crime; Insolvency Proceedings; Civil Litigation Proceedings; Tax Proceedings